2018
DOI: 10.1016/j.envint.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, variability, and predictors of urinary bisphenol A levels in 50 North Carolina adults over a six-week monitoring period

Abstract: Bisphenol A (BPA) is commonly manufactured to make polycarbonate plastics and epoxy resins for use in consumer products and packaged goods. BPA has been found in several different types of environmental media (e.g., food, dust, and air). Many cross-sectional studies have frequently detected BPA concentrations in adult urine samples. However, limited data are available on the temporal variability and important predictors of urinary BPA concentrations in adults. In this work, the major objectives were to: 1) qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 60 publications
6
42
0
1
Order By: Relevance
“…Although many studies report concentrations of EDCs by time of day of urine collection, few present data about month or season of data collection. In a cross-sectional study of 50 White, Black, and Hispanic adults aged 19–50 years in North Carolina in 2009, BPA concentrations were highest in winter and spring, 73 while, in the Canadian Maternal-Infant Research on Environmental Chemicals (MIREC) study, a cohort study of 2,001 pregnant women (mean age: 32 years) recruited in 2008–2011, BPA concentrations were highest in fall and winter. 74, 75 In an analysis of 177 pregnant women (mean age: 35.7 years; recruited in 2005–2011) from the Environment and Reproductive Health Study (EARTH), an open cohort study of mostly White women and men recruited from a fertility clinic in Boston, MA, 76 adjustment for season of urine collection had no influence on paraben concentrations, 9 indicating little association between season and methyl paraben concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies report concentrations of EDCs by time of day of urine collection, few present data about month or season of data collection. In a cross-sectional study of 50 White, Black, and Hispanic adults aged 19–50 years in North Carolina in 2009, BPA concentrations were highest in winter and spring, 73 while, in the Canadian Maternal-Infant Research on Environmental Chemicals (MIREC) study, a cohort study of 2,001 pregnant women (mean age: 32 years) recruited in 2008–2011, BPA concentrations were highest in fall and winter. 74, 75 In an analysis of 177 pregnant women (mean age: 35.7 years; recruited in 2005–2011) from the Environment and Reproductive Health Study (EARTH), an open cohort study of mostly White women and men recruited from a fertility clinic in Boston, MA, 76 adjustment for season of urine collection had no influence on paraben concentrations, 9 indicating little association between season and methyl paraben concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the success of the intervention to reduce BPS exposure, results should be interpreted with caution given the relatively small sample size of this study and the large number of non-detectable BPA and BPF concentrations. Only spot urine samples were collected, which may have been insufficient to reliably estimate a long-term urinary bisphenol exposure as a recent study suggested that multiple samples over several days are needed [ 39 ]. Previous studies have shown that urinary BPA concentrations vary daily [ 40 ] and may be influenced by recent food intake [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A related study in Taiwan [3] pointed out that there was almost no risk of BPA intake through diet, and BPA was ingested by the human body mainly due to other exposures. Morgan [4] studied the content of BPA in the urine of 50 American adults and found that the median BPA concentration in human urine was 2.07 μg/L. Through their life contact observation, the proportion of BPA intake from the diet was about 20%, while contacting other sources seemly dominate.…”
Section: Introductionmentioning
confidence: 99%